2013
DOI: 10.1007/s00428-013-1487-0
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological and clinical findings in renal transplants with Banff type II and III acute cellular rejection without tubulointerstitial infiltrates

Abstract: According to the Banff guidelines for renal transplants, pure endothelialitis without any tubulointerstitial infiltrates (with the Banff components v ≥ 1, i0, t0) has to be called acute cellular rejection (ACR). The pathophysiology of this rare lesion abbreviated as v_only is currently unclear, as well as its clinical, serological, and prognostic implications. Therefore, we conducted this retrospective comparative study. We compared all 23 biopsies with v_only from Hannover Medical School between 2003 and 2010… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
1
4
1
Order By: Relevance
“…Banu Sis and colleagues presented their results during the 2013 Banff conference on allograft pathology, showing that biopsies with isolated v‐lesions are similar with regard to their response to treatment and graft survival to v‐lesions with concomitant interstitial inflammation and tubulitis, thus represent rejection . This is entirely in concordance with a recently published study comparing 23 biopsies with isolated v‐lesions with matched biopsies showing endothelialitis plus inflammation and biopsies without any evidence of rejection .…”
Section: Kidney Transplant Biopsy In Patients With Acutely Deterioratsupporting
confidence: 68%
“…Banu Sis and colleagues presented their results during the 2013 Banff conference on allograft pathology, showing that biopsies with isolated v‐lesions are similar with regard to their response to treatment and graft survival to v‐lesions with concomitant interstitial inflammation and tubulitis, thus represent rejection . This is entirely in concordance with a recently published study comparing 23 biopsies with isolated v‐lesions with matched biopsies showing endothelialitis plus inflammation and biopsies without any evidence of rejection .…”
Section: Kidney Transplant Biopsy In Patients With Acutely Deterioratsupporting
confidence: 68%
“…Our first goal was to address whether IvL represents a particular type of allograft rejection, either ABMR or TCMR. To do so, we chose, similarly to Wu et al 8 and unlike other studies, 6,[9][10][11]13 to do the follow- year posttransplantation showed no molecular signature of rejection. 13 These findings could suggest that mechanisms different from rejection, that is, endothelial injury related to ischemia-reperfusion, may operate in some cases of IvL.…”
Section: Graft Survivalmentioning
confidence: 99%
“…4 Arterial involvement is sufficient to classify IvL as type II or III acute TCMR if pathologists rigorously comply with the instructions of the "historical" Banff scheme. 6,[8][9][10][11] Therefore, this multicentric study was conducted to thoroughly characterize the clinicopathologic phenotype of patients with IvL. 7 However, the role of the humoral immune response in the pathophysiology of IvL remains unclear, as the incidence of DSAs has not been systematically addressed in previous studies focusing on IvL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 The interpretation of v-lesions without tubulointerstitial inflammation (i-t), isolated v-lesions, has been particularly difficult to resolve. A comparison of 23 biopsies with isolated v-lesions to 23 matched biopsies with inflammation was unable to identify significant differences 28 but underscored the concerns about ABMR.…”
mentioning
confidence: 99%